Growth and production response of plant pakcoy (brassica rapa l) on use of nasa light organic fertilizer - Lisdayani; Fitra Syawal Harahap; Putri Mustika Sari (Jurnal Pertanian Tropik, 2019)
Pakcoy (Brassica rapa L.) or commonly called mustard spoon includes vegetable plants that are heat resistant, so that they can be planted in the lowlands to highlands The production of packcoy plants experiencing ups and downs in 2010 is the peak production of 141.25 quality / ha and continues to decline to 2014 became 114.35 quality / ha. Efforts to increase packcoy production can be done by using organic fertilizers from agricultural waste, manure, green manure, human waste, and compost instead of nutrient sources. This study aims to determine the response of growth and production of Pakcoy plants to the provision of NASA POC organic fertilizer. This study uses factorial randomized block design consisting of 2 treatment factors, namely: Chicken Cage Organic Fertilizer (A) which consists of 3 levels, namely: A0 = 0 tons / ha, A1 = 15 tons / ha (158 g / polybag), A2 = 30 tons / ha (316 g / polybag). NASA POC concentration (N) consists of 4 levels, namely: N0 = 0% (control), N1 = 1 cc / liter of water, N2 = 2 cc / liter of water, N3 = 3 cc / liter of water. The results showed that NASA's POC showed a significant effect on pakcoy plant height, the use of liquid organic fertilizer dosage (2cc / ltr) had a significant effect on plant height. The highest pakcoy plant height is found in the treatment of N2 (2 cc / ltr) of 25.50 cm. The net weight per plot was obtained at the N2 treatment of 262.92 grams